Adsorption study of desulfurization of diesel oil using activated charcoal - Darwish, Noora Naif (2015)
A Master of Science thesis in Chemical Engineering by Noora Naif Darwish entitled, "Adsorption study of desulfurization of diesel oil using activated charcoal," submitted in May 2015. Thesis advisor is Dr. Zarook Shareefdeen. Soft and hard copy available.